(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
• This article discusses an innovative approach to the design, manufacture, and operation of high-precision measuring instruments based on the concept of a digital twin. The proposed method enables the creation of a highly accurate virtual copy of a physical measuring device that integrates data on component geometric errors, assembly errors, static and dynamic system errors, and sensor characteristics. A multi-stage procedure for constructing such a digital twin is described, from design to calibration and operation. The architecture of the system, consisting of the physical subsystem of the device, its digital twin, and an integrated measurement management subsystem, is presented. A key advantage of this approach is the ability to predict measurement uncertainty, monitor instrument accuracy degradation in real time, optimize measurement trajectories on the virtual model, and, as a result, significantly improve the quality, reliability, and life cycle of measuring equipment. The method is illustrated using the example of constructing a coordinate measuring machine.